2014
DOI: 10.1177/1071100714544521
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of Computed Tomography to Evaluate Ankle and Hindfoot Fusions

Abstract: Level IV, case series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…Third, in our study, weightbearing conventional radiographs were used to evaluate the fusion status. CT scans have been shown to have high reliability in determining the degree of successful fusion of the hindfoot [6]. However, in our study, only patients with a suspected nonunion or delayed union underwent CT, as it would be impractical to obtain CT in all patients.…”
Section: Discussionmentioning
confidence: 87%
“…Third, in our study, weightbearing conventional radiographs were used to evaluate the fusion status. CT scans have been shown to have high reliability in determining the degree of successful fusion of the hindfoot [6]. However, in our study, only patients with a suspected nonunion or delayed union underwent CT, as it would be impractical to obtain CT in all patients.…”
Section: Discussionmentioning
confidence: 87%
“…8 A later report correlated the degree of fusion identified on CT scan with the functional outcome and found that an arthrodesis area of 25% to 50% was necessary for clinical success. 5 The same study found no statistically significant interrater reliability for the evaluation of ankle fusion by CT scan in contrast to subtalar fusion, which had a high interrater reliability. 5 In our series, we did not use CT scan to assess ankle fusion.…”
Section: Discussionmentioning
confidence: 90%
“…11,13,14,16,33 CT has been described as being instrumental in determining the adequacy of arthrodesis in the foot and ankle. 5 An earlier report was not certain what percentage of radiographic fusion defines a successful arthrodesis. 8 A later report correlated the degree of fusion identified on CT scan with the functional outcome and found that an arthrodesis area of 25% to 50% was necessary for clinical success.…”
Section: Discussionmentioning
confidence: 99%
“…There is substantial disagreement in the literature regarding diagnostic criteria for arthrodesis nonunion. In addition, some recent articles have demonstrated clinical outcomes that diverge from the criteria commonly used in these cases 3 , 5, 6, 7, 8…”
Section: Discussionmentioning
confidence: 99%
“…Pseudoarthrosis, or nonunion, is one of the most frequent complications, occurring in up to 40% of cases 3 , 4 . The definition of consolidation after arthrodesis can be challenging in some scenarios 5, 6, 7, 8. Some factors require careful analysis, especially in cases with an equivocal outcome.…”
mentioning
confidence: 99%